Penerapan Etika Bisnis Islam Dalam Pemasaran Produk Multi Jasa Barokah Dengan Akad Murabahah Di BMT UGT Nusantara Capem Temuguruh - Munawir, Munawir; Anwarulloh, Ahmad Aikon (JPSDa: Jurnal Perbankan Syariah Darussalam, 2024)
This research aims to determine the Application of Islamic Business Ethics in Marketing Mukti Services Barokah Products with Murabahah Contracts at BMT UGT Nusantara Capem Temuguruh Banyuawangi. The results of the study show the application of Islamic business ethics in the marketing of multi-service Barokah products used by BMT UGT Nusantara Capem Temuguruh which have been identified as: optimizing Islamic business ethics in product marketing by providing honest, clear information and always maintaining behavior in product marketing so that customers are always comfortable in financing or depositing. When a customer wants to apply for multi-service product financing, for example, wants to buy a motorbike but doesn't have enough money, the customer goes to BMT to offer Murabahah financing, after submitting a diacc the BMT immediately buys the motorbike, after that the motorbike already belongs to BMT so the customer gets confirmation that the motorbike it is desirable that the customer has purchased it, then the customer enters into a ba'i al Murabahah contract with the terms agreed at the beginning of the BMT cost price to buy the owner of the motorbike plus BMT profit (margin), after that the customer gets relief to pay off the financing at BMT by means of monthly installments